CPEO and Mitochondrial Myopathy in a Patient with DGUOK Compound Heterozygous Pathogenetic Variant and mtDNA Multiple Deletions. (6th March 2019) - Montano, V.; Simoncini, C.; Calì, Cassi L.; Legati, A.; Siciliano, G.; Mancuso, M.
Abstract : The classic features of deoxyguanosine kinase ( DGUOK ) deficiency are infantile onset hepatic failure with nystagmus and hypotonia; mitochondrial DNA studies on affected tissue reveal mitochondrial DNA depletion. Later, it has been shown that the mutations in the same gene may present with adult-onset mitochondrial myopathy and mitochondrial DNA multiple deletions in skeletal muscle. Here we report the case of a 42-year-old Italian woman presenting with a chronic progressive external ophthalmoplegia and myopathy with mtDNA multiple deletions and the compound heterozygous c.462T>A (p.Asn154Lys) and c.707+2T>G pathogenic variants in DGUOK .